Modeliranje, analiza, sinteza in realizacija regulacijskih sistemov - Ritonja, Jožef (University of Maribor Press, 2020)
Modeling, analysis, synthesis and realization of control systems. The textbook covers all stages in the design of control systems. First, he thoroughly presents the methods for determining mathematical models. Methods for analyzing derived mathematical models are presented. Based on the acquired knowledge, a synthesis of control systems is made. The realization of discrete control systems is demonstrated.